Inbound Marketing: uma avaliação sobre a sua adoção em empresas de tecnologia - Moraes, Caetano Expedito Holanda de (2021)
The internet changed the consuming way in the world. Nowadays, we search in digital even before purchase. Because of that, many companies implemented strategies to attract customers on the internet. The business-to-business market also does it, due to the growing competitiveness of the market and the innovative need, especially in technology companies, which have complex products. Among these strategies, inbound marketing stands out in Brazil and, mainly, in the world. Their focus is retaining potential consumers in company social networks using content well ranked in search engines. Thus, this work aims to understand how technology companies in Ceará use inbound marketing to retaining potential consumers, describing their similarities and differences. The study used three analysis criteria to assess the strategies inbound marketing of Fortes Tecnologia, Casa Magalhães, and Boavista Tecnologia: the content distributed during the purchase journey; cross-media: dissemination in various media; o SEO: number of visitors, number of backlinks, and domain authority.